Twin pregnancy in which both fetuses have Cantrell's pentalogy: A case report and literature review. (May 2021) - Demir, Merve; Sertel, Emre; Ture, Mehmet Zeki
Abstract: Cantrell's pentalogy is a congenital multiple malformation consisting of midline supraumbilical thoraco-abdominal wall defects, anterior and pericardial diaphragm defects, lower sternum defects, ectopia cordis and various intracardiac anomalies. Complete pentalogy is very rare. Some additional anomalies may accompany pentalogy and there are cases in the literature where chromosomal anomalies and pentalogy are seen. Cases of Cantrell's pentalogy in twin pregnancies are rare. Twin pregnancies with Cantrell's pentalogy in both fetuses are one of the rarest cases in the literature. In this study, we presented a twin pregnancy case with Cantrell's pentalogy in both fetuses and we reviewed twin pregnancy cases in which Cantrell's pentalogy was seen in the literature. In our case, anomalies were found in both fetuses in the evaluation performed on a 32-year-old, gravida 2, para 1 woman with 10 weeks + 5 days monochorionic-monoamniotic twin pregnancy. The first fetus had ectopia cordis, cystic hygroma and increased nuchal thickness (4.6 mm), and the anterior abdominal wall was in contact with the amniotic band. The second fetus had ectopia cordis omphalocele, cystic hygroma, holoprosencephaly and a single lower extremity deficiency. Both fetuses were pre-diagnosed with Cantrell's pentalogy and the parents were informed about the adverse course of the fetuses. After the completion of the legal procedures, with the approval and decision of the parents, termination was made in the 11th week of pregnancy. External images of the fetuses confirmed the diagnosis. The family denied the autopsy procedure. When we review the literature, twin pregnancies complicated by Cantrell's pentalogy are divided into 3 groups: Group1- cases where one of the twins has completely normal phenotype and the other twin has Cantrell's pentalogy; Group2- cases where one of the twins has Cantrell's pentalogy and the other twin does not have the Cantrell's pentalogy but has several anomalies; Group3- cases where both fetuses have Cantrell's pentalogy. In conclusion, early diagnosis of twin pregnancy cases complicated by Cantrell's pentalogy and determination of all anomalies in both fetuses are very important in terms of obstetric management.